Technological characteristics of Pseudotsuga menziesii growing in Valdivia - Diaz-Vaz, J. E.; Cuevas, H.; Fernández, A.; Inzunza, L. (Bosque (Valdivia), 1988)
This study analizes some of the physical and mechanical properties of Douglas-fir trees from three stands located on the coast of the province of Valdivia, Chile. Specific gravity, skrinkage, tracheid length, compression parallel to grain, static bending, hardness Janka and nail withdrawal were determined. Average test results and their variability show a high similarity with species growing in the middle west of the United States.